Linking Incoterm Selection and Human Resource Competence for Enhancing Competitive Advantage: Evidence from Freight Forwarders Companies in Indonesia - Sugiono, Ahmad; Rahayu, Agus; Wibowo, Lili Adi; Hurriyati, Ratih (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The freight forwarding sector holds a pivotal role in facilitating international trade by coordinating cross-border goods movement and integrating diverse logistics functions. Strategic choices and organizational capabilities are critical in enabling firms to sustain competitiveness. Within this context, Incoterm selection combined with workforce competence is recognized as a central determinant of competitiveness. Accordingly, this study investigates the interplay between Incoterm decisions and human resource proficiency in strengthening the competitive advantage of Indonesian freight forwarding companies. Adopting a quantitative design, data were gathered from freight forwarders and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the proposed relationships. The findings reveal that both Incoterm selection and human resource competence have significant and positive influences on competitive advantage. Moreover, results suggest that competitive advantage is reinforced through the alignment of Incoterm choices with risk management, transportation modes, and negotiation capacity, while concurrently developing personnel skilled in customs procedures, global logistics systems, and intercultural communication. This research contributes to logistics and supply chain management literature by integrating contractual decision-making perspectives with resource-based theory. The study provides practical insights for freight forwarders in enhancing their market position within the global trade environment.